Viabilitas sel fibroblas BHK-21 pada permukaan resin akrilik rapid heat cured (Viability of fibroblast BHK-21 cells to the surface of rapid heat cured acrylic resins) - Anita Yuliati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
Acrylic resins are widely used in the fabrication of denture bases and have been shown to be cytotoxic as a result of substances that leach from the resin. Numerous reports suggest that residual monomer may be responsible for mucosal irritation and sensitization of tissues. This information is important in eddition to the information of the biologiced effect of such materials. The purpose of this study was to know the viability of fibroblast BHK-21cells to the surface of rapid heat cured acrylic resins. The sample of 5 mm in diameter and 1 mm thickness was cured in water bath for 20, 30, and 40 minutes at 100° C. BHK-21 cells were grown in medium eagle to be 2 × 105 cell/ml in 96 well micro titer plates as the added sample and incubated at 37° C for 24 hour. Five hours before the end of the incubation MTT solutionwas added from step one to each well containing cells. Viability cells were measured by spectrophotometer at 550 nm. The data were statistically analyzed by using one-way analysis of variance followed by LSD test. The result indicated that viability of fibroblast BHK-21 cells did not decrease to the surface of resin acrylic rapid heat cured.